Proposing a Neurotropic Etiology for Acute Posterior Multifocal Placoid Pigment Epitheliopathy and Relentless Placoid Chorioretinitis - Steptoe, Paul J.; Pearce, Ian; Beare, Nicholas A.V.; Sreekantam, Sreekanth; Mohammed, Bashar R.; Barry, Robert J.; Steeples, Laura R.; Denniston, Alastair K.; Murray, Philip I. (Frontiers in Ophthalmology, 2022)
Purpose: To reassess the underlying pathophysiology of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) and relentless placoid chorioretinitis (RPC) through comparison with the non-inoculated eye of the von Szily animal model of neurotropic viral retinal infection. Methods: Narrative review. Results: Literature reports of isolated neurotropic viral entities and rising serological viral titers in APMPPE after presentation support a potential direct infective etiology. In general, viral transport along axons results in mitochondrial stasis and disruption of axoplasmic flow. Clinical manifestations of axoplasmic flow disruption in APMPPE/RPC may signify the passage of virus along the neuronal pathway. From a case series of 11 patients, we demonstrate a timely, spatial, and proportional association of optic disc swelling with APMPPE lesion occurrence. Signs within the inner retina appear to precede outer retinal lesions; and acute areas of outer nuclear layer (ONL) hyperreflectivity appear to be the result of coalescence of multiple hyperreflective foci resembling axonal spheroids (which occur as a consequence of axoplasmic disruption) and follow the Henle fiber layer neurons. Underlying areas of retinal pigment epithelium (RPE) hyper-autofluorescence follow ONL hyperreflectivity and may signify localized infection. Areas of apparent choriocapillaris hypoperfusion mirror areas of RPE/Bruch’s membrane separation and appear secondary to tractional forces above. Increases in choroidal thickness with lesion occurrence and focal areas of choriocapillaris hypoperfusion are observed in both APMPPE/RPC and the von Szily model. Conclusions: The neurotrophic infection model provides significant advantages over the existing primary choriocapillaris ischemia hypothesis to account for the range of imaging signs observed in APMPPE and RPC.